Cognitive Symptom Management and Rehabilitation Therapy (CogSMART) for Traumatic Brain Injury. Treatment manual (ukrainian version). 2nd part: sessions 5-8 - Twamley Елізабет; Noonan Сара; Savla Ґаурі; Schiehser Дон; Jak Емі; Assonov Дмитро; Ukrainska Яна; Komova Жанна; Osadchyi Артем; Chaban Олег; Khaustova Олена (Psychosomatic Medicine and General Practice, 2021)
CogSMART is a cognitive training program for people with traumatic brain injury (TBI). It aims to improve the skills of perspective memory, attention, executive functions (problem solving, planning, cognitive flexibility) in order to more successfully perform daily activities and achieve personal, work and study goals. CogSMART is based not on a large number of trainings and tasks, but on a compensatory cognitive training — improving cognitive skills by using certain adaptation strategies and removing obstacles. The use of CogSMART has already shown good results in the cognitive rehabilitation of people with traumatic brain injury in the United States. The translation of the manual was performed by specialists of the Kyiv City Clinical Hospital for War Veterans with further scientific editing of the text by professors of the Department of Medical Psychology, Psychosomatic Medicine and Psychotherapy at Bogomolets National Medical University. With the permission of Dr. Elizabeth Twamley, the author of the original program, the Ukrainian version of the manual is published in the journal and is available for Ukrainian-speaking audience. The program contains 12 sessions. This part of the Ukrainian version of the manual presents the sessions 5 – 8 of CogSMART. Sessions 1 - 4 can be found in the first part of the translated manual via this link. This part of the Ukrainian version of the manual presents sessions 5 - 8 of the CogSMART program. The 5th session is dedicated to the training of perspective memory, and is a logical continuation of the 4th session. Participants can learn how to effectively use the calendar and link tasks, as well as train making to-do lists and other short-term memory strategies. Session 6 focuses on attention and concentration. In this session, participants can learn about concentration difficulties after traumatic brain injury and practice strategies to improve attention skills. Session 7 continues the analysis of attention. In this session, participants can master the skills of vigilance during a conversation and discuss how strategies for focusing can help with long-term goals. Session 8 is dedicated to learning and memory. It aims to introduce the concepts of memory, to train new strategies for memorizing information. This material can be useful for clinical psychologists, occupational therapists, psychotherapists and specialists in related fields who help people with traumatic brain injury and conduct a cognitive rehabilitation or cognitive training.